The Reality of Illiteracy in Egypt, India and Saudi Arabia: A Comparative Study - Al-khaldi, Fawzia Hamdan; Al-Mobeeriek, Haifa Fahad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of illiteracy in Egypt and India, and the efforts undertaken by governmental and private institutions to combat the phenomenon in those two countries through a comparative study, and the study used the comparative analytical method. The results indicated that associations have a major role in eradicating illiteracy in society, and this role must be strengthened, and it is necessary that private sector supports the governmental and charitable sectors, through donations in view of the social responsibility of this sector. In addition, increasing the illiteracy rate among females requires raising families’ awareness and reducing Early marriage and child labor. By reviewing these two experiences, the study recommended the need to develop a strategic plan according to the Kingdom’s 2030 vision to eradicate illiteracy in the Kingdom. All components of Saudi society participate in drawing up the plan and encourage decentralization in literacy programs and teacher preparation programs, so that implementation is flexible according to the circumstances of each of the Kingdom regions, and thus move away from those programs from stereotyped.